Sport supplementation in competitive swimmers: a systematic review with meta-analysis - Raúl Domínguez; Inmaculada López-León; Javier Moreno-Lara; Esteban Rico; Antonio J. Sánchez-Oliver; Ángela Sánchez-Gómez; Javier Pecci (Journal of the International Society of Sports Nutrition)
Background Competitive swimmers have a high prevalence of sports supplement (SS) consumption. However, only a few SS are scientifically proven to be safe, effective, and legal. Therefore, before incorporating supplements to enhance performance and health in competitive swimming, it is crucial to conduct an analysis and review to assess their effects. The objective of this study was to analyze the demonstrated effects of SS, as reported in published studies, on the swimming performance of competitive swimmers.Methods Following PRISMA guidelines, a systematic search was conducted across six databases for the selection of studies included in this review. Studies that analyzed the effects of sports supplementation compared to placebo were included and subjected to meta-analysis.Results This revision included 23 studies, 16 of them (69.6%) qualified as excellent and 7 (30.4%) as good at the methodological level based on the punctuation in the PEDro scale. The systematic review included 422 swimmers (61.8% male, 38.2% female), with distances assessed ranging from 50 m to 800 m, including studies employing interval procedures. Creatine showed a significant effect (ES = −0.46; 95% CIs = −0.75 to −0.17, p = 0.002; I2 = 11%) on swimming performance, while the rest of the analyzed supplements did not show significant effects (all p > 0.05).Conclusions Creatine supplementation demonstrated ergogenic benefits for competitive swimmers, although the evidence supporting the use of this supplement is still limited. Sodium bicarbonate and β-alanine may enhance performance in distances with higher glycolytic demands, while caffeine is effective at dosages of 3–6 mg/kg administered 60 min before exercise. Further research is needed to confirm the potential ergogenic effects of other supplements, such as beetroot juice.